GSD analysis for the generation of cartography using drone technology, huaca from the Universidad Nacional Mayor de San Marcos - Quispe Enriquez, Omar Christian (2015)
In this article, experimentally and using the Ground Sample Distance (GSD) parameter, the relationship between the drone's flight height and the identification of objects for the generation of cartography is analyzed. Scheduled flights were made at different heights, with respect to the takeoff level and considering the height of the huaca of the Universidad Nacional Mayor de San Marcos, using a multi-rotor drone, which generated orthophotos with different GSD and allowed to conclude the potential use of the drone to large-scale mapping generation.